The Meaning of Death in Islam and Christianity: A Conceptual and Spiritual Analysis - Maranatha, Christian Ade (Perkumpulan Teolog Agama Kristen Indonesia, 2024)
The concept of death has been a subject of human contemplation across various religious and philosophical traditions. Both Islam and Christianity provide their followers with distinct interpretations of death, offering perspectives on the afterlife and how death should be approached. This study aims to compare the understanding of death in Islam and Christianity, exploring theological differences and similarities between the two religions. Using a qualitative approach through literature review, the research examines religious texts, scholarly articles, and other sources to analyze how death is perceived and how each religion encourages its followers to prepare for it. The findings reveal that while both religions view death as a transition to the afterlife, Islam focuses on the journey to the barzakh and ultimate judgment, while Christianity emphasizes salvation through faith in Jesus Christ and eternal life with God. This comparative study provides deeper insight into how both religions shape their followers’ views on mortality and the afterlife. Contribution: This study contributes to the understanding of how Islamic and Christian teachings on death influence the behavior and attitudes of their followers toward life and mortality. It provides a framework for interfaith discussions on the spiritual implications of death and afterlife.